¿De homínidos a post-humanos? Algunos desafíos del transhumanismo - Berzosa Martínez, Cecilio Raúl (Razón y fe, 2019)
The article is summarized in this question: How to be human in a world that no longer wants to be human? We talk about transhumanism and post-humanism, giving prominence to four realities (NBIC): nanotechnology, biotechnology, Big Data and artificial intelligence. At the same time, we try to respond from the tradition of French thought, asking to what Christian anthropology and theology can contribute.